Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Explore in-depth answers to your questions from a knowledgeable community of experts across different fields. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Let's find the inverse of the function [tex]\( g(x) = \frac{5}{x-3} + 6 \)[/tex] step-by-step.
1. Start with the original function:
[tex]\[ g(x) = \frac{5}{x-3} + 6 \][/tex]
2. Replace [tex]\( g(x) \)[/tex] with [tex]\( y \)[/tex] to facilitate finding the inverse:
[tex]\[ y = \frac{5}{x-3} + 6 \][/tex]
3. Interchange [tex]\( x \)[/tex] and [tex]\( y \)[/tex] (this is effectively saying to solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]):
[tex]\[ x = \frac{5}{y-3} + 6 \][/tex]
4. Isolate the fraction by subtracting 6 from both sides:
[tex]\[ x - 6 = \frac{5}{y-3} \][/tex]
5. To isolate [tex]\( y \)[/tex], multiply both sides by [tex]\( y-3 \)[/tex]:
[tex]\[ (x - 6)(y - 3) = 5 \][/tex]
6. Distribute [tex]\( x - 6 \)[/tex] on the left-hand side:
[tex]\[ xy - 3x - 6y + 18 = 5 \][/tex]
7. Rearrange the terms to isolate those containing [tex]\( y \)[/tex] on one side:
[tex]\[ xy - 6y = 3x - 13 \][/tex]
8. Factor out [tex]\( y \)[/tex] on the left-hand side:
[tex]\[ y(x - 6) = 3x - 13 \][/tex]
9. Solve for [tex]\( y \)[/tex] by dividing both sides by [tex]\( x - 6 \)[/tex]:
[tex]\[ y = \frac{3x - 13}{x - 6} \][/tex]
So, the inverse of the function [tex]\( g(x) = \frac{5}{x-3} + 6 \)[/tex] is:
[tex]\[ g^{-1}(x) = \frac{3x - 13}{x - 6} \][/tex]
This is in line with the given solution.
1. Start with the original function:
[tex]\[ g(x) = \frac{5}{x-3} + 6 \][/tex]
2. Replace [tex]\( g(x) \)[/tex] with [tex]\( y \)[/tex] to facilitate finding the inverse:
[tex]\[ y = \frac{5}{x-3} + 6 \][/tex]
3. Interchange [tex]\( x \)[/tex] and [tex]\( y \)[/tex] (this is effectively saying to solve for [tex]\( x \)[/tex] in terms of [tex]\( y \)[/tex]):
[tex]\[ x = \frac{5}{y-3} + 6 \][/tex]
4. Isolate the fraction by subtracting 6 from both sides:
[tex]\[ x - 6 = \frac{5}{y-3} \][/tex]
5. To isolate [tex]\( y \)[/tex], multiply both sides by [tex]\( y-3 \)[/tex]:
[tex]\[ (x - 6)(y - 3) = 5 \][/tex]
6. Distribute [tex]\( x - 6 \)[/tex] on the left-hand side:
[tex]\[ xy - 3x - 6y + 18 = 5 \][/tex]
7. Rearrange the terms to isolate those containing [tex]\( y \)[/tex] on one side:
[tex]\[ xy - 6y = 3x - 13 \][/tex]
8. Factor out [tex]\( y \)[/tex] on the left-hand side:
[tex]\[ y(x - 6) = 3x - 13 \][/tex]
9. Solve for [tex]\( y \)[/tex] by dividing both sides by [tex]\( x - 6 \)[/tex]:
[tex]\[ y = \frac{3x - 13}{x - 6} \][/tex]
So, the inverse of the function [tex]\( g(x) = \frac{5}{x-3} + 6 \)[/tex] is:
[tex]\[ g^{-1}(x) = \frac{3x - 13}{x - 6} \][/tex]
This is in line with the given solution.
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.